Comments on "Economic policy for the European Community - the way forward". Selection of comments prepared for a Kiel Symposium on the report of the Group of Rome - Herbert Giersch; Gottfried Haberler; Jan Tumlir; Juergen B. Donges; Bela Balassa; Fritz Machlup; Johann Schollhorn; Norbert Walter; Pascal Salin; Roland Vaubel; Willi Albers; Fritz Neumark; et al. (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1975)
Table of Contents: Herbert Giersch, Gottfried Haberler, Jan Tumlir, Juergen B. Donges, Bela Balassa, Europe's Role in the World Economy; Fritz Machlup, Johann Schollhorn, Norbert Walter Pascal Salin, Roland Vaubel, Roads to Monetary Union; Willi Albers, Fritz Neumark, Carl S. Shoup, Dieter Biehl, Fiscal Harmonization; Dieter Biehl, Bela Balassa, Claus Noe, Sebastian Schnyder, The Scope of a Common Regional Policy; Adolf Weber, Tim Josling, New Approaches to Structural Policy? Reforming the Common Agricultural Policy; Gerhard Prosi, Gerhard Fels, Klaus Stegemann, New Approaches to Structural Policy? Industrial Policy, Competition and Social Progress
Keywords: 330